Effect of cooking and in vitro digestion on the antioxidant activity of dry-cured ham by-products. (July 2017) - Gallego, Marta; Mora, Leticia; Hayes, Maria; Reig, Milagro; Toldrá, Fidel
Abstract: Dry-cured ham by-products have been traditionally used in Mediterranean household cooking of broths and stews. The aim of this work was to evaluate the effect of cooking treatments and in vitro gastrointestinal digestion on the antioxidant activity of natural peptides found in bones from Spanish dry-cured hams. The antioxidant activity was tested using five different assays and results demonstrated that cooking using conventional household methods increased the antioxidant activity of ham by-products when assessed using different antioxidant assays with the exception of the ABTS radical scavenging measurement assay. Simulated gastrointestinal digestion showed no significant effect on the antioxidant activity of ham by-products and antioxidant activity decreased when assessed using the ORAC and β-carotene bleaching assays. Analysis by MALDI-TOF MS revealed a considerable breakdown of peptides due to the action of gastrointestinal enzymes, mainly in samples cooked at 100 °C for 1 h. In addition, 459 peptides derived from 57 proteins were identified and quantified using mass spectrometry in tandem, evidencing that peptides derived from collagen protein were responsible for the differences in antioxidant activities observed between the uncooked and cooked samples after digestion. The results show the potential of dry-cured ham bones as a source of antioxidant peptides that retain their bioactivity after household cooking preparations and gastrointestinal digestion. Graphical abstract: Highlights: Cooking and in vitro digestion on the antioxidant activity of broths was evaluated. Cooking increased the antioxidant activity of ham by-products. Collagen peptides were responsible for the antioxidant differences between samples. Dry-cured ham bones has resulted a potential source of antioxidant peptides.